2008
DOI: 10.1093/jpepsy/jsn064
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Somatic Complaints in Children with Recurrent Abdominal Pain and Anxiety Disorders

Abstract: RAP and anxiety are closely related. Further understanding between these disorders is essential to understanding the development and progression of RAP, and to inform the prevention and treatment of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 27 publications
7
89
0
10
Order By: Relevance
“…This study extends the literature linking pediatric FAP to anxiety disorders 7,10,11,50 with prospective data showing that patients with FAP continue to experience high rates of anxiety disorders into adolescence and young adulthood. Patients with FAP also had high rates of depressive disorders during their lifetime, but few met criteria for a depressive disorder at the time of follow-up.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This study extends the literature linking pediatric FAP to anxiety disorders 7,10,11,50 with prospective data showing that patients with FAP continue to experience high rates of anxiety disorders into adolescence and young adulthood. Patients with FAP also had high rates of depressive disorders during their lifetime, but few met criteria for a depressive disorder at the time of follow-up.…”
Section: Discussionsupporting
confidence: 74%
“…9 In addition, pediatric patients with FAP have high rates of anxiety and depression. 10,11 Although several studies have evaluated the persistence of abdominal pain in patients with FAP, 12 only 1 study evaluated diagnostic criteria for psychiatric disorders in these patients when they reached adulthood. In their seminal study, Campo et al 13 identified 28 pediatric patients with medically unexplained recurrent abdominal pain by retrospective chart review and conducted telephone interviews with these patients when they were young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Even though most children with frequent AP are lacking explanatory organic diseases [1] and a substantial proportion of children exhibits psychological problems [14,17,52], it cannot be concluded that frequent nonorganic AP is caused by psychological factors [11]. FGIDs are thought to be strongly linked to a disordered brain-gut interaction [13]: Stress and unpleasant emotional states lead to hypervigilance and hence to an increase of arousal of the autonomous nervous system and the endocrine system, which may contribute to a heightened sensitivity of the gut and modified gut motility [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…A part of children with AP is at risk of symptom persistence till adulthood [5,21,24,53]. Children with AP are found to score higher in questionnaires assessing psychopathological symptoms especially internalizing disturbances such as anxiety and other somatic complaints [14,17,52]. They also feature a high rate of psychiatric disorders such as anxiety disorders and depression [4,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation